Meningkatkan Hasil Pertanian Warga melalui Revitalisasi Embung di Desa Rejosari Kecamatan Bantur Kabupaten Malang - M Yusuf Azwar Anas; Eko Setya Aliansyah (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2022)
The embung in the curse hamlet is a source of air that flows even though it is dry, especially in the curse hamlet. Before the embung was formed, it was originally a ravine that was found in a dry river around 1997 - 1998. When heavy rains poured water onto the roads. When it dries, the river dries up so the people of Dusun Kutukan have difficulty getting water. In 1998 the community took the initiative to form an embung to collect water. So that when the dry season arrives, the people of Dusun Kutukan have a supply of water for their daily needs. Initially this reservoir was made by the people of Dusun Kutukan which functioned as meeting the needs of clean water. However, gradually the fulfillment of clean water can extend to the fulfillment of water for the people of Rejosari Village. In the first year, activities focused on preparing infrastructure, including the construction of curse water reservoirs, deepening and renovation, lighting around the embung and planting flowers to make them look beautiful and cool. The success of this first-phase program is the basis for building Kutukan Village, Rejosari Village, which is independent and prosperous based on local potential. The village built this embung to overcome the limited water sources in Rejosari Village. These thresholds are used to meet household and irrigation needs. The operation of the embung needs to be planned because the storage volume is limited. Optimization of the use of water from the reservoir is needed to determine the amount of water use in the scenario of rainy conditions